A Survey of Basketball Extracurricular Activity Management Practices in Indonesian High Schools - Nurma Hesti; Mohamad Annas Mohamad Annas (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to analyze the management of basketball extracurricular at SMA Negeri 14 Semarang from the aspects of planning, organizing, implementing, and evaluating, as well as identifying obstacles faced in its implementation. This study uses a qualitative approach with a descriptive method. The research subjects include school principals, coaches, coaches, and students involved in extracurricular activities. Data collection techniques are carried out through observation, interviews, and documentation, while data analysis uses data reduction techniques, data presentation, and conclusion drawn. The results of the study show that basketball extracurricular management has been carried out in accordance with the management function. Planning is carried out through the preparation of training programs that adjust the academic calendar, organization involves a clear division of tasks, regular implementation with a fairly good level of student activity, and evaluations are carried out periodically. However, there are still obstacles in the form of limited facilities and infrastructure as well as consistency of student attendance. The conclusion of this study is that the management of basketball extracurricular at SMA Negeri 14 Semarang has been running quite well, but it needs to be improved in terms of facilities and student discipline so that the goals of coaching can be achieved optimally.